2020
DOI: 10.7759/cureus.8070
|View full text |Cite
|
Sign up to set email alerts
|

Acute Necrotizing Encephalitis in Viral Respiratory Tract Infection: An Autopsy Case Report

Abstract: Acute necrotizing encephalitis (ANE) is a rare complication of viral respiratory tract infections, with specific histological changes. The condition is most commonly described in the pediatric population, however, it can also develop in the elderly, with some genetic factors being described as contributory. Herein, we report the autopsy finding of a patient with a viral respiratory tract infection, complicated with ANE. The patient was a 77-year-old female with multiple comorbidities living in a social home. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Based on the clinical studies and the limited neuropathological data, CNS histopathology encompasses hypoxic/ischemic encephalopathy, activated microglial cells with variable infiltration of perivascular T lymphocyte, cerebrovascular diseases, AHNE, encephalitis/meningitis, acute myelitis, demyelinating disorders, and PNS involvement [ 21 , 68 , 71 , 73 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ], with histologically documented lesions in some studies [ 6 , 11 , 68 , 69 , 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the clinical studies and the limited neuropathological data, CNS histopathology encompasses hypoxic/ischemic encephalopathy, activated microglial cells with variable infiltration of perivascular T lymphocyte, cerebrovascular diseases, AHNE, encephalitis/meningitis, acute myelitis, demyelinating disorders, and PNS involvement [ 21 , 68 , 71 , 73 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ], with histologically documented lesions in some studies [ 6 , 11 , 68 , 69 , 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Severe COVID-19 cases, therefore, are at high risk of thrombosis secondary to an indirect hypercoagulable state and a direct vascular endothelial damage [ 116 ]. In AHNE, coagulative neuronal necrosis, reactive gliosis, and perivascular lymphocytic infiltration with cell debris or inclusions were the main histological aspects [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Postmortem examination is known as the most definitive mean to assess viral neuroinvasion in patients with COVID‐19 14 . Since Paniz‐Mondolfi et al 46 reported the first autopsy evidence of SARS‐CoV‐2 viral particles in the brain parenchyma of a COVID‐19 patient by electron microscopy and PCR assays on April 21, 2020, increasing autopsy studies on patients with COVID‐19 have been published 39,46‐72 …”
Section: Discussionmentioning
confidence: 99%
“…The cerebral MRI of the first patient with SARS-CoV-2-associated AHNE displayed a hemorrhagic rim enhancing lesions within the thalami, medial temporal lobes, and subinsular regions [ 19 ]. AHNE was also reported in a 59-year-old woman with anemia, seizures, and somnolence [ 21 ] and, on autopsy, in a polymorbid 77-year-old woman [ 22 ].…”
Section: Discussionmentioning
confidence: 99%